Artificial intelligence empowered combat systems from the perspective of Agent - LIU Wei, XIE Haibin, CHEN Shaofei (Zhihui kongzhi yu fangzhen)
Aiming at the intelligent design of combat systems, we proposed a conceptual framework and application methods of Agent based on artificial intelligence technology. First, we analyze the concept of Agent and discusse the important significance of studying Agent in the combat system. Then, we introduce the research framework of artificial intelligence based on Agent, and multiple application methods of Agent in combat systems. Finally, we analyze the development trends of Agent technology and the risks and challenges that its combat applications may face.